2021
DOI: 10.1590/1806-9282.20210755
|View full text |Cite
|
Sign up to set email alerts
|

Side effects and antibody response of an inactive severe acute respiratory syndrome coronavirus 2 vaccine among health care workers

Abstract: OBJECTIVE: This study aims to investigate the antibody response and the side effects of the two-dose inactive SARS-CoV-2 vaccine (CoronaVac, Sinovac, China) among a health care worker population in Turkey. METHODS:This study was a prospective, cross-sectional, single-center study conducted between December 16, 2020, and March 15, 2021. We evaluated the side effects from a questionnaire, and anti-spike immunoglobulin G response to the vaccine (0-and 28-day schedule) using an enzyme-linked immunosorbent assay.RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Therefore, our study presents a contrast that warrants further investigation using larger and more comprehensive datasets. Our study also revealed a statistically significant decrease in AEFI incidence following the second dose, which is consistent with the findings of Gümüş et al, where the general side effects were 37.2% and 28.7% after the first and second doses, respectively [14]. Similarly, the most frequently observed AEFI, localized pain at the injection site (15.7% and 11.6%, respectively), were in line with our data.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, our study presents a contrast that warrants further investigation using larger and more comprehensive datasets. Our study also revealed a statistically significant decrease in AEFI incidence following the second dose, which is consistent with the findings of Gümüş et al, where the general side effects were 37.2% and 28.7% after the first and second doses, respectively [14]. Similarly, the most frequently observed AEFI, localized pain at the injection site (15.7% and 11.6%, respectively), were in line with our data.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the studies that did not find a relationship between exposure to smoking and COVID-19 vaccine response, current smokers tended to have predominant lower antispike IgG levels than the past and never smoker groups, but the difference was not statistically significant in two reports [25,26]. Similarly, smoking status did not correlate with titres of IgG against the spike protein induced by BNT162b2 mRNA COVID-19 vaccine in the study of Modenese et al [43], or those induced by either BNT162b2 or BBIBP-CorV COVID-19 vaccine in Alqassieh et al [36].…”
Section: Resultsmentioning
confidence: 86%
“…It is worth also mentioning that some studies included in this review did not detect a correlation between smoking status and postvaccination IgG titres. However, most of these reports include a very low sample size and/or proportion of smokers [25,32,34,43], or examined the antibody levels in the early weeks after the completion of vaccination cycle [25,32,43], making it difficult to appreciate possible differences between smokers and nonsmokers [20].…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen cohort and cross-sectional studies assessed associations between anti-S and adiposity (BMI, waist circumference) following COVID-19 vaccinations. The directionality of associations was inconsistent [ 86 ]; specifically, 7 studies showed null associations [ [87] , [88] , [89] , [90] , [91] , [92] , [93] ], 3 found positive associations [ 81 , 94 , 95 ], and 3 showed inverse associations [ [96] , [97] , [98] ]. Anti-S levels were evaluated in all studies except for one that assessed seroprevalence [ 88 ].…”
Section: Anti-s Binding Antibodiesmentioning
confidence: 99%
“…The directionality of associations was inconsistent [ 86 ]; specifically, 7 studies showed null associations [ [87] , [88] , [89] , [90] , [91] , [92] , [93] ], 3 found positive associations [ 81 , 94 , 95 ], and 3 showed inverse associations [ [96] , [97] , [98] ]. Anti-S levels were evaluated in all studies except for one that assessed seroprevalence [ 88 ]. Based on the previous observation of the J-shaped association between BMI and mortality, future studies should consider the nonlinearity of this association.…”
Section: Anti-s Binding Antibodiesmentioning
confidence: 99%